Managing canopy cover to preserve forest microclimate and diverse macroarthropod communities in times of drought - Verdonck, Sanne; De Win, Yannick; Nutter, Thomas; Van Meerbeek, Koenraad; Thomaes, Arno; De Smedt, Pallieter; Dekoninck, Wouter; Hendrickx, Frederik; Muys, Bart (The Journal of applied ecology, 2025)
Forest canopies play a vital role in buffering macroclimatic conditions, creating stable microclimates that support species unable to survive under the surrounding climate. However, disturbances driven by climate change alongside management interventions can disrupt canopy cover, altering forest microclimates and, consequently, forest‐related biodiversity. To investigate these dynamics, we monitored forest floor temperature, soil moisture and macroarthropod communities along a canopy cover gradient in the National Park Brabantse Wouden, Belgium. Forest microclimate was recorded using TMS4‐loggers throughout the 2022–2023 growing seasons. Macroarthropod activity‐density and species richness were sampled using pitfall traps during the 2022 summer. Generalized linear mixed models and piecewise structural equation modelling were used to assess the influence of forest structure. As canopy cover decreased, microclimate temperatures became more similar to macroclimate temperatures, reducing the forest's thermal buffering capacity. Once canopy cover dropped below 50%, temperatures were amplified rather than buffered. Additionally, lower stand densities were linked to higher soil moisture levels. Microclimatic conditions significantly affected both the activity‐density and species richness of macroarthropod communities. Woodlice profited from temporarily elevated forest floor temperatures if soil moisture was sufficient, while prolonged high temperatures negatively affected ground beetles. Ground beetles benefited from reduced canopy cover and increased deadwood, while woodlice preferred oak‐dominated stands. Synthesis and applications. To sustain a stable and well‐buffered microclimate, we recommend maintaining canopies as closed as possible. Even small openings reduce the forest's ability to buffer temperature, with canopy covers below 50% leading to temperature amplification. Closed canopies should be combined with isolated canopy gaps to promote habitat heterogeneity. Additionally, deadwood amounts should increase to provide shelter during droughts. This balanced management approach fosters stable forest microclimates and diverse habitats, supporting long‐ and short‐term macroarthropod biodiversity in temperate broadleaf forests. To sustain a stable and well‐buffered microclimate, we recommend maintaining canopies as closed as possible. Even small openings reduce the forest's ability to buffer temperature, with canopy covers below 50% leading to temperature amplification. Closed canopies should be combined with isolated canopy gaps to promote habitat heterogeneity. Additionally, deadwood amounts should increase to provide shelter during droughts. This balanced management approach fosters stable forest microclimates and diverse habitats, supporting long‐ and short‐term macroarthropod biodiversity in temperate broadleaf forests.